THE FORMULATION POLICY FOR PROSECUTORâS AUTHORITY WITHIN MONEY LAUNDERING - Paramita, Indah (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The authority of money laundering caseâs prosecutors mentioned in article 68 Law Nr. 8 Year 2010 concerning the prevention and eradication of money laundering. The formulation remains unclear and needs further juridical interpretation. Based on the result of research, it can be concluded that the prosecutorâs authority formulated in article 68 Law Nr. 8 Year 2010 concerning the prevention and eradication of money laundering contains of weaknesses asÂ  follow : (1)in indictment making process, (2) in caseâs handing over process and (3) in transaction blockaging. The juridical implication that appear is the technical regulation should be dismissed since they are in contrary with higher regulation (Law Nr. 8 Year 2010 concerning the prevention and eradication of money laundering). With regards to this condition, the best future formulation for prosecutorâs authority is appliying Indonesian Criminal Procedure Codification (KUHAP), since it can decrease the authority overlap between District Attorney and Corruption Eradication Commission.Keywords : Formulation, authority, prosecutor.